One Step Polishing System Difference on Bulk-Fill Composite Resin Microhardness, Surface Roughness, and Color Stability - Aristiyanto, Regia; Rahmanita, Almira; Cahyo, Galih Hanur; Lastanta, Septa Intan (Odonto : Dental Journal, 2023)
Background: The polishing procedure was an important step in composite resin restoration as it reduces restoration surface roughness. Smooth and well-polished restoration surfaces can increase microhardness and minimize discoloration on the tooth surface. The study aims to examine the differences of one-step polishing systems on surface roughness, microhardness, and color stability of bulk-fill composite resin. Method: The samples were bulk-fill composite resin moulded with 4 mm of diameter and thickness (n=30) for microhardness (n=15) and surface roughness (n=15) test and moulded with 6 mm of diameter and 4 mm of thickness for color stability (n=15) test. The samples were divided into three groups consisting of 5 samples for each variable and were polished using PoGo, OptraPol, and OneGloss. Color stability test samples were immersed in tea solution for 7 days. Color stability measurement was done by comparing the results of color measurements using a spectrophotometer before and after immersion. Microhardness was tested using Vickers Microhardness Tester, while surface roughness was tested using the Stylus Profilometer Fowler Surfcorder SE1700. Result: The data analysis showed that PoGo produced the smoothest surface roughness significantly (p=0.006), the highest microhardness significantly (p=0.002), and the lowest color change significantly (p = 0.027) Conclusion: PoGo produced lowest surface roughness and color change, and highest microhardness compare with OptraPol and OneGloss.